Pipeline and method for degrading PFOS (perfluorooctane sulfonate) by utilizing mechanical energy of water flow
By loading the PVDF composite piezoelectric layer on the inner wall of the water treatment pipeline, the piezoelectric effect is stimulated by using the mechanical energy of the water flow, the problems of low PFOS degradation efficiency and high energy consumption in the prior art are solved, and the PFOS degradation effect with low energy consumption and defluorination is achieved.
Patent Information
- Application Number
- CN202411882379.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-02-28
AI Technical Summary
Existing water treatment technologies are difficult to effectively degrade PFOS, and there are risks and economic unreasonable problems in high energy input and use of additional agents.
A PFOS degradation pipeline using mechanical energy of water flow is used to load a PVDF composite piezoelectric layer on the inner wall of the pipeline, and the piezoelectric effect is stimulated by the water flow to catalyze the degradation of PFOS.
It realizes in-situ, low energy consumption, defluorination of PFOS, avoids additional energy input and drug use, and is energy-saving and environmentally friendly.
Smart Images

Figure CN119528282A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of water treatment, and in particular to a PFOS degradation pipeline and method utilizing mechanical energy of water flow. Background Art
[0002] The abundant high-energy C−F bonds in PFOS (perfluorooctane sulfonate) molecules are the main reason for its chemical and biological resistance to degradation. Incomplete defluorination may even lead to unknown secondary risks. Defluorination mineralization is the key to completely remove the environmental risks of PFOS. Existing water treatment technologies, such as adsorption removal, have risks such as failure to destroy its structure and secondary pollution. The reported PFOS reduction-oxidation synergistic degradation systems based on light and electrocatalysis usually require high-density energy input (UV / electricity), which may be inefficient and uneconomical when treating low-concentration PFOS in water. In addition, the use of some sacrificial agents (such as sulfites, indole derivatives and other photogenerated precursors) may also introduce additional risks. The defluorination effect of PFOS treatment technology based on single advanced oxidation or reduction is not ideal. Summary of the invention
[0003] The object of the present invention is to provide a PFOS degradation pipeline and method utilizing the mechanical energy of water flow.
[0004] In the first aspect, the present invention provides a PFOS degradation pipeline using mechanical energy of water flow; the pipeline includes a pipeline body and a PVDF composite piezoelectric layer loaded on the inner wall of the pipeline body. The PVDF composite piezoelectric layer is prepared by doping a semiconductor nano-piezoelectric material into a PVDF piezoelectric matrix material; oxygen vacancies are introduced into the semiconductor nano-piezoelectric material.
[0005] Preferably, the mass fraction of the semiconductor nano-piezoelectric material in the PVDF composite piezoelectric layer is 50% to 95% (preferably 80%).
[0006] Preferably, the piezoelectric coefficient of the semiconductor nanopiezoelectric material is greater than 10 pC / N and satisfies any one or more of the following conditions: Condition 1. The conduction band potential is lower than the reduction potential of the β-position CF bond of PFOS.
[0007] Condition 2: The valence band potential is higher than the oxidation potential at which the α-position CC bond of PFOS dissociates.
[0008] Preferably, the semiconductor nano-piezoelectric material is a ZnO nano-rod or perovskite with oxygen vacancies introduced; the oxygen vacancies in the semiconductor nano-piezoelectric material are introduced by annealing in an oxygen-deficient atmosphere.
[0009] Preferably, the PVDF composite piezoelectric layer is obtained by adding PVDF doped with semiconductor nano-piezoelectric material to an organic solvent to obtain a composite emulsion, and loading the composite emulsion on the inner wall of the pipeline body in a phase transition manner.
[0010] Preferably, the pipeline body is a PTFE pipeline.
[0011] Preferably, the pipeline body adopts a bellows structure.
[0012] In a second aspect, the present invention provides a method for preparing a PFOS-degradable pipeline using mechanical energy of water flow, which comprises the following steps: Step 1: Preparation of ZnO nanorods containing oxygen vacancies (ZnO-Vo): using zinc acetate and sodium hydroxide as raw materials and anhydrous ethanol as solvent to react and synthesize ZnO nanorods; annealing the obtained ZnO nanorods in a nitrogen atmosphere to introduce oxygen vacancies; Step 2: Preparation of ZnO-Vo / PVDF composite piezoelectric material: adding ZnO nanorods PVDF doped with oxygen vacancies into an organic solvent to obtain a ZnO-Vo / PVDF composite emulsion.
[0013] Step 3: Construction of PFOS degradation pipeline: The ZnO-Vo / PVDF composite emulsion prepared in step 2 is coated on the inner wall of the pipeline body to form a PVDF composite piezoelectric layer.
[0014] In a third aspect, the present invention provides a PFOS degradation method using mechanical energy of water flow, which uses the aforementioned PFOS degradation pipeline; the PFOS degradation method is as follows: the PFOS degradation pipeline is connected in series to a treated PFOS wastewater delivery pipeline, so that the PFOS wastewater flows through the PFOS degradation pipeline; the PVDF piezoelectric matrix material and PFOS produce FF interaction, so that PFOS is enriched on the inner wall of the PVDF composite piezoelectric layer; the water flow impacts the PVDF composite piezoelectric layer, so that the PVDF composite piezoelectric layer is excited, and catalytic degradation of PFOS is carried out under the action of the piezoelectric effect.
[0015] Preferably, the pH value of the treated water body is 3-9; a periodically changing pressure is applied to the input PFOS degradation pipeline through a water flow driving device, so that the PVDF composite piezoelectric layer is subjected to periodic impact.
[0016] The present invention has the following beneficial effects: 1. The present invention aims at addressing the shortcomings of the current PFOS catalytic degradation technology in water, such as the need for high-density energy drive. Based on the real environmental characteristics of the water treatment system and the characteristics of piezoelectric materials, the present invention utilizes the abundant low-frequency water flow mechanical energy in the pipeline to drive piezoelectric catalysis, and regulates the catalytic activity of the material through dual piezoelectric coupling and interface effect, thereby constructing an in-situ, low-energy consumption, defluorination degradation method for PFOS in water. This method does not require additional energy input and additional agents, is in line with the development direction of water treatment technology, and has distinct energy-saving characteristics.
[0017] 2. The piezoelectric catalytic degradation of PFOS by the present invention is the result of the synergistic effect of the oxidation and reduction processes, that is, PFOS is adsorbed and enriched on the surface of the ZnO-Vo / PVDF composite piezoelectric layer under the interaction of FF, and the ZnO-Vo / PVDF composite piezoelectric layer is periodically deformed under the action of water flow, which triggers the generation and separation of piezoelectric carriers. Finally, holes participate in the oxidative degradation of PFOS through direct oxidation and indirect oxidation by generating •OH, while electrons mainly participate in the oxidative degradation of PFOS through direct reduction and generating •O 2 - Indirectly participate in the reduction process, among which direct oxidation of holes contributes the most.
[0018] 3. The present invention uses PTFE pipe as the pipe body. The PTFE pipe and the PVDF composite piezoelectric layer have good affinity under the FF interaction, which is conducive to the loading of the composite piezoelectric material on the inner wall of the pipe, improving the degradation efficiency, and maintaining the stability of the PFOS degradation pipe in long-term use.
[0019] 4. The present invention successfully prepared a ZnO-Vo / PVDF composite piezoelectric layer with good piezoelectric response performance by using solvent thermal synthesis and phase conversion coating method. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A schematic diagram of the preparation and testing process of the PFOS degradation pipeline provided by the present invention; Figure 2 Electron micrographs of ZnO nanorods, ZnO-Vo, PVDF, and ZnO-Vo / PVDF; Figure 3 This is a comparison chart of the PVDF piezoelectric matrix before and after doping with ZnO-Vo; Figure 4 The crystal phase diagrams of ZnO nanorods, ZnO-Vo, and ZnO-Vo / PVDF; Figure 5 FTIR spectra of ZnO / PVDF, PVDF, and ZnO-Vo / PVDF; Figure 6PFM piezoelectric amplitude and phase images of ZnO-Vo / PVDF film (parts a and b are the stereoscopic and top-down perspectives of the amplitude image, respectively, and part c is the phase image); Figure 7 This is a diagram showing the cyclic removal effect of PFOS by the test device provided in an embodiment of the present invention.
[0021] Figure 8 The figure is a comparison chart of PFOS degradation effects of different piezoelectric films (part a corresponds to the degradation amount curve, and part b corresponds to the degradation rate curve).
[0022] Fig. 9 This is a comparison chart of PFOS degradation effects of ZnO-Vo / PVDF film at different stirring speeds; Fig.10 The comparison chart of PFOS degradation effect of ZnO-Vo / PVDF film at different pH values; Fig.11 This is a comparison of the PFOS degradation effects of ZnO-Vo / PVDF film with the addition of different free radical scavengers; DETAILED DESCRIPTION
[0023] The present invention will be further described below in conjunction with the accompanying drawings.
[0024] Example like Figure 1 As shown, a PFOS degradation pipeline using mechanical energy of water flow includes a pipeline body and a PVDF composite piezoelectric layer loaded on the inner wall of the pipeline body. During operation, the treated water containing PFOS is input into the pipeline body; the PVDF composite piezoelectric layer is impacted by the water flow of the treated water body; thus, the mechanical energy of the water flow is used to stimulate the PVDF composite piezoelectric layer in the pipeline body, and the piezoelectric effect of the material is used to catalyze the degradation of PFOS.
[0025] During the working process, the PVDF material and the PFOS in the treated water can produce FF interaction, so that the low concentration PFOS in the treated water is enriched on the inner wall of the PVDF composite piezoelectric layer, thereby improving the degradation efficiency of PFOS.
[0026] In some embodiments, the pipeline body adopts a PTFE pipeline, so that the inner wall of the pipeline body and the PVDF composite piezoelectric layer have good affinity under the FF interaction, which is beneficial to the loading of the composite piezoelectric material on the inner wall of the pipeline, improving the degradation efficiency, and maintaining the stability of the PFOS degradation pipeline in long-term use.
[0027] In some embodiments, the pipeline body adopts a bellows structure to provide abundant water flow impact energy for water flow drive, which is conducive to the excitation of piezoelectric effect.
[0028] This embodiment couples piezoelectric catalysis with a water flow driven pipeline to achieve in-situ, low-carbon degradation of PFOS.
[0029] The PVDF composite piezoelectric layer is obtained by doping ZnO nanorods into a PVDF piezoelectric matrix material.
[0030] Due to the high activation energy of PFOS redox, low concentration in water, and insufficient piezoelectric response of piezoelectric materials, piezoelectric catalytic degradation of PFOS faces technical challenges such as low reaction rate. To this end, in this embodiment, oxygen vacancies are introduced into ZnO nanorods by annealing to form ZnO-Vo; the oxygen vacancies on the surface of ZnO-Vo can enrich the binding sites of F and Zn atoms in PFOS molecules, shortening the mass transfer distance between carriers or active free radicals and pollutants.
[0031] In this embodiment, the mass fraction of ZnO-Vo doped in the PVDF composite piezoelectric layer is 80%.
[0032] The microstructures of ZnO nanorods, ZnO-Vo obtained by introducing oxygen vacancies into ZnO nanorods, PVDF piezoelectric matrix materials, and PVDF composite piezoelectric layers introduced with ZnO-Vo are shown in Figure 2. Figure 2 The morphology comparison between the PVDF piezoelectric matrix material and the PVDF composite piezoelectric layer introduced with ZnO-Vo is shown in Figure 3 The crystal phases of ZnO nanorods, ZnO-Vo, and ZnO-Vo / PVDF are shown in Figure 4 As shown; the FTIR spectra of ZnO / PVDF, PVDF, and ZnO-Vo / PVDF are shown Figure 5 shown.
[0033] from Figure 2 and Figure 3 It can be seen that the ZnO prepared by the solvothermal method has a slender rod-like structure, about 300-500nm long, and a smooth surface; 2 The oxygen vacancy ZnO obtained after annealing still maintains a rod-like structure, but its length is shortened to 200-300 nm, and its surface becomes rough and porous. This may be due to the breakage of the nanorods caused by uneven heating during the annealing process, and the defects caused by the escape of O on the crystal surface; the oxygen vacancies on the surface of ZnO-Vo can enrich the binding sites of F atoms and Zn atoms in PFOS molecules, shortening the mass transfer distance between carriers or active free radicals and pollutants. In addition, Figure 2It can also be seen that the PVDF piezoelectric film has a mesh porous structure. When doped with ZnO-Vo, the ZnO nanorods are attached to the mesh PVDF fibers. The mesh porous film structure provides a large specific surface area, which provides abundant reaction sites for catalytic reactions and is beneficial to the degradation of pollutants. At the same time, the rod-like structure of zinc oxide nanorods can increase the piezoelectric response. In addition, doping PVDF with ZnO promotes the transformation of PVDF from the non-polar α phase to the piezoelectrically active β phase, which helps to improve the response of the piezoelectric film to low-frequency mechanical energy and improve the catalytic activity.
[0034] from Figure 4 It can be seen that 31.7 o , 34.4 o and 36.2 o The diffraction peaks at represent the (100), (001) and (101) crystal planes of ZnO nanorods, respectively, which indicates that the prepared ZnO mainly grows along the C-axis. The same phase exposure as that of ZnO nanorods was detected in the ZnO-Vo / PVDF film, indicating the successful doping of ZnO-Vo, and PVDF is also mainly distributed in the β phase. Figure 5 It can be seen that the absorption peak representing β-PVDF (868 cm -1 and 1403 cm -1 ) is significantly enhanced after PVDF is doped with ZnO or ZnO-Vo, which indicates that the doping of ZnO nanorods promotes the transformation of PVDF from the non-polar α phase to the piezoelectrically active β phase. This helps to improve the response ability of the piezoelectric film to low-frequency mechanical energy and improve the catalytic activity. This verifies the successful preparation of the ZnO-Vo / PVDF catalytic film in this example.
[0035] The piezoelectric response of ZnO-Vo / PVDF composite film was characterized by piezoelectric force microscopy (PFM). Figure 6 The strength of the piezoelectric response can be expressed by the vibration amplitude and phase at the same position of the membrane; Figure 6 There is a clear contrast between parts a and b. Figure 6 The 180° domain is shown in part c, indicating that the ZnO-Vo / PVDF composite film exhibits good piezoelectricity in a certain polarization direction.
[0036] The piezoelectric properties of all samples were studied using a quasi-static d33 measuring instrument (YE2730A). The piezoelectric constant of PVDF before loading ZnO-Vo was 3.1; the piezoelectric constant of PVDF after loading ZnO-Vo was 5.4; it can be seen that the piezoelectric constant of ZnO-Vo / PVDF is 1.74 times that of PVDF, indicating that the doping of ZnO-Vo improves the piezoelectric properties.
[0037] In some embodiments, a heterojunction structure can be constructed on the PVDF composite piezoelectric layer to change the band gap structure of the PVDF composite piezoelectric layer, promote the separation of piezoelectric carriers, and improve the piezoelectric response capability, thereby improving the catalytic efficiency of the piezoelectric catalyst.
[0038] The preparation process of the PFOS degradation pipeline using water flow mechanical energy is as follows: (1) Preparation of ZnO (V0) nanorods: ZnO nanorods were synthesized in a high pressure reactor using zinc acetate and sodium hydroxide as raw materials and anhydrous ethanol as solvent; the obtained ZnO nanorods were annealed in a nitrogen atmosphere in a tubular furnace to introduce oxygen vacancies. In this embodiment, the annealing conditions were: annealing at 600°C for 4 hours.
[0039] (2) Preparation of ZnO-Vo / PVDF composite piezoelectric material: Using DMF as solvent, ZnO nanorods were doped into PVDF to obtain ZnO-Vo / PVDF composite emulsion.
[0040] (3) Construction of PFOS degradation pipeline: The ZnO-Vo / PVDF composite emulsion prepared in step (2) is loaded on the inner wall of the PTFE corrugated tube through phase transformation to form a PVDF composite piezoelectric layer.
[0041] A test device is designed to verify the treatment effect of this embodiment on PFOS. The test device includes a water flow driving device and the aforementioned PFOS degradation pipeline. The input port and the output port of the water flow driving device are respectively connected to the two ends of the PFOS degradation pipeline to form a circulation loop. In this embodiment, the water flow driving device adopts a peristaltic pump; the test device realizes the piezoelectric catalytic degradation of PFOS by pumping water by the peristaltic pump, and samples are taken in different time periods of 0-10h to analyze the PFOS degradation rate and defluorination rate; multiple batches are circulated to compare the changes in PFOS degradation rate and defluorination rate and life status between different batches.
[0042] The initial concentration of PFOS was 4.0 mM; the pumping flow rate was 500 mL / min; Figure 7 As shown in the figure, after three consecutive cycles, the removal efficiency of the system remained above 93.3%, with good stability.
[0043] In some other embodiments, the ZnO(V0) nanorods can be replaced by other semiconductor nanopiezoelectric materials (such as perovskite); the piezoelectric coefficient of the replacement semiconductor nanopiezoelectric material is greater than 10 pC / N and satisfies any one or more of the following conditions: Condition 1. The conduction band potential is lower than the reduction potential of the β-position CF bond breaking (the value is -1.0 V vs SHE); Condition 2. The valence band potential is higher than the oxidation potential of the α-position CC bond dissociation (the value is +3.0 V vs SHE).
[0044] The treatment object of the PFOS degradation pipeline using the mechanical energy of water flow in this embodiment can be PFOS sewage, wastewater, or unused domestic water (including drinking water).
[0045] In some other embodiments, the pipeline body is made of transparent material, such as glass; some minerals in glass can increase the piezoelectric coefficient of PVDF; the pipeline body made of transparent material can allow the treated water to be exposed to light in the PFOS degradation pipeline, further improving the PFOS degradation efficiency.
[0046] In some embodiments, the treated water input into the PFOS degradation pipeline is provided with pulse pressure through a water flow driving device (such as a water pump), so that the pressure of the treated water in the PFOS degradation pipeline changes periodically, so that the PVDF composite piezoelectric layer is subjected to periodic impact, thereby improving the degradation efficiency of the PVDF composite piezoelectric layer on PFOS; in this case, the pipeline body can use a smooth inner wall structure instead of a bellows structure.
[0047] Experimental Example 1 In order to determine the difference in degradation effects of PVDF composite piezoelectric layers with different doping conditions, a comparative experiment was conducted; the experimental group and the control group were set as follows: Experimental group 1: PVDF composite piezoelectric layer doped with 80% ZnO-Vo by mass.
[0048] Experimental group 2: PVDF composite piezoelectric layer doped with 50% ZnO-Vo by mass.
[0049] Control group 1: PVDF composite piezoelectric layer was doped with 80% by mass of ZnO nanorods without annealing to form oxygen vacancies.
[0050] Control group 2: The PVDF composite piezoelectric layer uses pure PVDF.
[0051] The experimental conditions of the experimental group and the control group were the same; specifically, they were as follows: equal amount of mother liquor, stirring speed (600 rpm), pH = 7, and reaction at room temperature for 10 h. 1 mL of the reaction solution was sampled at 0 h, 0.5 h, 1 h, 2 h, 4 h, 6.5 h, and 10 h, respectively, and filtered through a 0.2 μm pore size water system (PES) filter membrane, and the samples were analyzed by LC-MS / MS.
[0052] The catalytic degradation effects of the PFOS degradation pipelines provided by the experimental groups 1 and 2 and the control groups 1 and 2 were compared. Figure 8 As shown. Figure 8 From part a, it can be seen that the PVDF composite piezoelectric layer with a ZnO-Vo doping rate of 80% has the best degradation effect, and the PFOS degradation rate reaches 98.1% in 6.5h.
[0053] The degradation rate fitting results of the PFOS degradation pipelines provided by experimental groups 1, 2 and control groups 1, 2 are as follows: Figure 8 As shown in part b, the composite films with different ZnO-Vo doping ratios have consistent catalytic activity (k 50%ZnO-Vo / PVDF =k 80%ZnO-Vo / PVDF = 1.046 h -1 ). This shows that the oxygen vacancies on the surface of ZnO-Vo can promote the separation of piezoelectric endogenous carriers (piezoelectric electrons and holes), increase the concentration of carriers, and thus facilitate the direct or indirect participation of carriers in the degradation of PFOS. In addition, the oxygen vacancies on the surface of ZnO-Vo may also enrich the binding sites of F and Zn atoms in the PFOS molecule, shortening the mass transfer distance between carriers or active free radicals and pollutants.
[0054] Experimental Example 2 For the PVDF composite piezoelectric layer obtained by doping 80% of ZnO-Vo, a comparative experiment of different driving mechanical energies was carried out; specifically: the degradation effect was tested at stirring rates of 0, 450 rpm, 600 rpm, and 720 rpm respectively; the results are shown in Fig. 9 shown; from Fig. 9 It can be seen that with the increase of stirring speed, the degradation rate of PFOS continues to increase. When the stirring rate reaches 720 rpm, PFOS basically reaches degradation equilibrium within 4 h, and the degradation rate is 98.0%; while at a speed of 600 rpm, PFOS still has not reached degradation equilibrium at 10 h, and the total degradation rate (92.5%) is also lower than the high mechanical driving force condition. Under lower mechanical force drive (450 rpm), PFOS reaches degradation equilibrium at about 6.5 h, but the degradation rate is only 75.4%. This shows that the strength of the driving mechanical energy not only affects the catalytic activity (degradation rate) of the piezoelectric film, but also affects the catalytic ability (degradation efficiency); therefore, the use of a pipe body with a bellows structure in this embodiment helps to improve the PFOS degradation effect.
[0055] Experimental Example 3 PFOS may be present in different proportions of non-ionized CF under different pH conditions. 3 (CF 2 ) 7 SO 3 H and ionized CF 3 (CF 2 ) 7 SO 3 -Coexistence. Different forms of PFOS may affect its adsorption behavior at the catalyst interface and its reaction affinity with active species, resulting in different degradation efficiencies. To this end, this embodiment conducts comparative experiments on different pH values of treated water bodies for PVDF composite piezoelectric layers obtained by doping 80% of ZnO-Vo; specifically, the degradation effect of treated water bodies containing PFOS at pH values of 3, 7, and 9 is tested respectively; the results are as follows: Fig. 9 As shown in the figure, when the pH of the system is neutral or acidic, PFOS degrades rapidly within 1 h, and the degradation rate is close to 80%. In the same period of time, the degradation rate of PFOS in an alkaline environment is only 6.3%. However, as the reaction time increases, the degradation rate of PFOS in an alkaline environment accelerates, and finally the total degradation efficiency of PFOS in 10 h under different pH conditions exceeds 96%, and the digestion efficiency is not greatly affected by the pH value. This shows that the different existence forms of PFOS mainly affect the initial step of its degradation, but have little effect on the degradation efficiency of the piezoelectric film. According to the literature, the ionization equilibrium constant of PFOS, pKa ≤ 1.0, which means that in an acidic environment, PFOS mainly exists in a non-ionic state, which may be conducive to the non-polar adsorption of PFOS on the PVDF surface.
[0056] Experimental Example 4 The degradation mechanism of PFOS by piezoelectric catalysis is studied as follows: By adding different free radical trapping agents into the system to inhibit the action of the corresponding active species and observing the changes in the PFOS degradation efficiency, the type of active species that play a key role in PFOS degradation and their contribution can be determined. EDTA-2Na is a hole inhibitor, KBrO 3 is an electron capture agent, tert-butyl alcohol (TBA) is an •OH capture agent, and pBQ is •O 2 - Capture Agent [9] .explain
[0057] The results are as follows Fig.11 As shown in the figure, EDTA-2Na has the strongest inhibitory effect on the degradation efficiency of PFOS, followed by TBA, KBrO 3 This indicates that the degradation of PFOS by ZnO-Vo / PVDF film piezoelectric catalysis is the result of the combined action of multiple active species, including holes, electrons, •OH and •O 2 - They all play a role in the PFOS degradation process. Generally, •OH comes from the active species indirectly generated by the oxidation of water molecules by holes; and •O 2 - It may come from the active species indirectly produced by the reduction of dissolved oxygen by piezoelectric electrons; therefore, it can be considered that the piezoelectric degradation of PFOS is the result of the synergistic effect of oxidation and reduction reactions.
[0058] Through research, it is found that single oxidation (such as •OH-mediated advanced oxidation) or single reduction reaction (such as photogenerated electron-mediated reduction) has limited effect on the degradation of perfluorinated compounds, while the synergistic oxidation and reduction process can achieve efficient conversion of intermediates of different properties by both, thus producing a chain reaction-like effect, which has significant potential for rapid degradation of PFAS (including PFOA and PFOS). The key to achieving efficient synergy of oxidation and reduction processes lies in the rational design of catalysts to achieve efficient separation of carriers (holes and electrons); at the same time, creating an environment that is conducive to the oxidation and reduction active species to interact with the reactants. In the present invention, due to the characteristics of piezoelectric screening charge, oxidative regions and reductive regions can be generated simultaneously in different regions of material deformation, and the oxidation-reduction characteristics of the regions can undergo periodic changes according to the periodic material deformation; at the same time, the oxygen vacancies of ZnO-Vo promote the separation of intrinsic carriers, and the specific adsorption of PFOS by PVDF enables the active species to be efficiently utilized by pollutants on the surface of the catalyst; the combined effect of the above factors leads to the degradation of PFOS by ZnO-Vo / PVDF film through oxidation-reduction synergy.
Claims
1. A PFOS degradation pipeline utilizing mechanical energy of water flow; comprising a pipeline body; characterized in that: The invention also includes a PVDF composite piezoelectric layer loaded on the inner wall of the pipeline body. The PVDF composite piezoelectric layer is prepared by doping semiconductor nano-piezoelectric materials into the PVDF piezoelectric matrix material; oxygen vacancies are introduced into the semiconductor nano-piezoelectric material.
2. The PFOS degradation pipeline utilizing water flow mechanical energy according to claim 1, characterized in that: The mass fraction of the semiconductor nano-piezoelectric material in the PVDF composite piezoelectric layer is 50% to 95%.
3. The PFOS degradation pipeline utilizing water flow mechanical energy according to claim 1, characterized in that: The piezoelectric coefficient of the semiconductor nanopiezoelectric material is greater than 10 pC / N and satisfies any one or more of the following conditions: Condition 1. The conduction band potential is lower than the reduction potential of the β-position CF bond of PFOS; Condition 2: The valence band potential is higher than the oxidation potential at which the α-position CC bond of PFOS dissociates.
4. The PFOS degradation pipeline using water flow mechanical energy according to claim 3, characterized in that: The semiconductor nano-piezoelectric material adopts ZnO nano-rods or perovskites with oxygen vacancies introduced; the oxygen vacancies in the semiconductor nano-piezoelectric material are introduced by annealing in an oxygen-deficient atmosphere.
5. The PFOS degradation pipeline using water flow mechanical energy according to claim 1, characterized in that: The PVDF composite piezoelectric layer is obtained by adding PVDF doped with semiconductor nano-piezoelectric material into an organic solvent to obtain a composite emulsion, and loading the composite emulsion on the inner wall of the pipeline body.
6. The PFOS degradation pipeline using water flow mechanical energy according to claim 1, characterized in that: The pipeline body is made of PTFE pipeline.
7. The PFOS degradation pipeline using water flow mechanical energy according to claim 1, characterized in that: The pipeline body adopts a bellows structure.
8. The method for preparing a PFOS-degradable pipeline using water flow mechanical energy as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Preparation of ZnO nanorods containing oxygen vacancies: using zinc acetate and sodium hydroxide as raw materials and anhydrous ethanol as solvent to react and synthesize ZnO nanorods; annealing the obtained ZnO nanorods in an oxygen-deficient atmosphere to introduce oxygen vacancies; Step 2: Preparation of ZnO-Vo / PVDF composite piezoelectric material: adding ZnO nanorods PVDF doped with oxygen vacancies into an organic solvent to obtain a ZnO-Vo / PVDF composite emulsion.
9. Step 3: Construction of PFOS degradation pipeline: The ZnO-Vo / PVDF composite emulsion prepared in step 2 is coated on the inner wall of the pipeline body to form a PVDF composite piezoelectric layer.
10. A method for degrading PFOS using mechanical energy of water flow, characterized in that: Using the PFOS degradation pipeline as claimed in claim 1; the PFOS degradation method is as follows: connecting the PFOS degradation pipeline in series to a pipeline for transporting a treated water body containing PFOS, so that the treated water body flows through the PFOS degradation pipeline; the PVDF piezoelectric matrix material and PFOS generate FF interaction, so that PFOS is enriched on the inner wall of the PVDF composite piezoelectric layer; The water flow impacts the PVDF composite piezoelectric layer, causing the PVDF composite piezoelectric layer to be excited and catalytically degrade PFOS under the action of the piezoelectric effect.
11. The method for degrading PFOS by using water flow mechanical energy according to claim 9, characterized in that: The pH value of the treated water body is 3-9; a periodically changing pressure is applied to the input PFOS degradation pipeline through a water flow driving device, so that the PVDF composite piezoelectric layer is subjected to periodic impact.
Citation Information
Patent Citations
Enrichment method of organic fluorides in water samples based on fluoride solid phase extraction technology
CN106124672A
Solid phase microextraction head for enriched perfluoro compound and preparation method thereof
CN108499549A
Reinforced piezoelectric stack piezoelectric energy harvesting device used for water flow pipelines
CN110391767A
Method for rapidly removing perfluoro / polyfluoro compounds in environmental water
CN111252859A
Preparation of flexible piezoelectric liner tube and application of flexible piezoelectric liner tube in self-driven degradation of organic pollutants
CN114804299A